Odpowiedzi

2009-12-08T00:25:09+01:00
2. a.) 6x²y - 3xy² = 3xy(2x - y) b.) 2xyz² - 4xy + 6x = 2x(yz² - 2y + 3) 3. a) n²(n - 1)(n² + 1) = (n³ - n²)(n² + 1) = n⁵ - n⁴+ n³ - n² b) n²(n+1)(n²-1) = (n³ + n²)(n² - 1) = n⁵ + n⁴- n³ - n²
4 3 4
2009-12-08T00:29:05+01:00
A) 6x2y-3xy2= 3xy(2x-y) b)2xyz2-4xy+6x=2x(yz2-2y+3) a) n2(n-1)(n2+1)= (n3-n2)(n2+1)=n5+n3-n4-n2 b) n2(n+1)(n2-1)= n2(n3-n+n2-1)= n5-n3+n4-n2
2 3 2
2009-12-08T00:35:26+01:00
Najlepsza Odpowiedź!
2009-12-08T01:06:16+01:00
A]6x²y-3xy²=3xy(2x-y),,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, b]2xyz²-4xy+6x=2x(yz²-2y+3) ,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,,, 2a]n²(n-1)(n²+1)=(n³-n²)(n²+1)=n⁵+n³-n⁴-n²=n²(n³+n-n²-1),,,,,,,,,,, b]n²(n+1)(n²-1)=(n³+n²)(n²-1)=n⁵-n³+n⁴-n²=n²(n³-n+n²-1)
6 4 6